SRSF2 safeguards efficient transcription of DNA damage and repair genes - Wagner, Rebecca E.; Arnetzl, Leonie; Britto-Borges, Thiago; Heit-Mondrzyk, Anke; Bakr, Ali; Sollier, Etienne; Gkatza, Nikoletta A.; Panten, Jasper; Delaunay, Sylvain; Sohn, Daniela; Schmezer, Peter; Odom, Duncan T.; et al. (Cell reports, 2024)
The serine-/arginine-rich splicing factor 2 (SRSF2) plays pivotal roles in pre-mRNA processing and gene transcription. Recurrent mutations, particularly a proline-to-histidine substitution at position 95 (P95H), are common in neoplastic diseases. Here, we assess SRSF2’s diverse functions in squamous cell carcinoma. We show that SRSF2 deletion or homozygous P95H mutation both cause extensive DNA damage leading to cell-cycle arrest. Mechanistically, SRSF2 regulates efficient bi-directional transcription of DNA replication and repair genes, independent from its function in splicing. Further, SRSF2 haploinsufficiency induces DNA damage without halting the cell cycle. Exposing mouse skin to tumor-promoting carcinogens enhances the clonal expansion of heterozygous Srsf2 P95H epidermal cells but unexpectedly inhibits tumor formation. To survive carcinogen treatment, Srsf2 P95H+/− cells undergo substantial transcriptional rewiring and restore bi-directional gene expression. Thus, our study underscores SRSF2’s importance in regulating transcription to orchestrate the cell cycle and the DNA damage response.